b) 6 . {[(75 - 5.13). 5 - 43] · 7+1}.
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
6 ×{[(75 - 5.13)×5 - 43] × 7+1}.=6×(69,87×5-43)×7+1=12.867,7
virgilpopescu1967:
Răspuns incorect.
Răspuns de
3
Răspuns:
6×{[(75-65)×5-43]×7+1}=
6×[(10× 5-43)×7+1]=
6×[(50-43)×7+1]=
6×(7×7+1)=
6×(49+1)=
6×50=
300
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba rusă,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
9 ani în urmă
Istorie,
9 ani în urmă